Microtensile bond strength of CAD/CAM-fabricated polymer-ceramics to different adhesive resin cements - Leyla Sadighpour; Farideh Geramipanah; Zahra Ghasri; Mehrnoosh Neshatian (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the microtensile bond strength (µTBS) of polymer-ceramic and indirect composite resin with 3 classes of resin cements.Materials and MethodsTwo computer-aided design/computer-aided manufacturing (CAD/CAM)-fabricated polymer-ceramics (Enamic [ENA; Vita] and Lava Ultimate [LAV; 3M ESPE]) and a laboratory indirect composite resin (Gradia [GRA; GC Corp.]) were equally divided into 6 groups (n = 18) with 3 classes of resin cements: Variolink N (VAR; Vivadent), RelyX U200 (RXU; 3M ESPE), and Panavia F2 (PAN; Kuraray). The μTBS values were compared between groups by 2-way analysis of variance and the post hoc Tamhane test (α = 0.05).ResultsRestorative materials and resin cements significantly influenced µTBS (p < 0.05). In the GRA group, the highest μTBS was found with RXU (27.40 ± 5.39 N) and the lowest with VAR (13.54 ± 6.04 N) (p < 0.05). Similar trends were observed in the ENA group. In the LAV group, the highest μTBS was observed with VAR (27.45 ± 5.84 N) and the lowest with PAN (10.67 ± 4.37 N) (p < 0.05). PAN had comparable results to those of ENA and GRA, whereas the μTBS values were significantly lower with LAV (p = 0.001). The highest bond strength of RXU was found with GRA (27.40 ± 5.39 N, p = 0.001). PAN showed the lowest µTBS with LAV (10.67 ± 4.37 N; p < 0.001).ConclusionsWhen applied according to the manufacturers' recommendations, the µTBS of polymer-ceramic CAD/CAM materials and indirect composites is influenced by the luting cements.